Analyzing Lexical Density and Readability in IELTS Band 4 Students’ Writing Test - Putri, Aqia Syahnayya; Anshary, Elvira Putri; Sinar, T. Silvana; Maharani, Puan (TALENTA, 2024)
This study explores the lexical density and readability levels of writing produced by IELTS Band 4 students. The main objectives are to assess the lexical density and readability of their writing across ten writing tests. The study employs a descriptive qualitative research method, using data collected from 10 writing tests conducted by IELTS Band 4 students. Lexical density is determined using the